Regarding of the color for the mineral silicate stain used on CC3 & CC5 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request to determine the color for the mineral silicate stain for BRACU new campus project.